FINAL INVESTMENT DECISION (FID) PROCESS IMPROVEMENT IN OIL & GAS MAJOR CAPITAL PROJECT. CASE STUDY OF PT. VUL’S DECISION-MAKING PROCESS - Marco Wibisono (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2022)
Uncertainties from many factors, oil price, production, execution and operational risks, external factors, are issues that impact project profitability. For major capital projects (MCPs), with magnitude of investment well into hundreds of millions or billions of dollars, a robust, structured rational process is required to minimize uncertainties and provide all the required information for a decision maker to make a high-quality, measured decision in continuing with execution of the project.Semi-structured interview for projects with CAPEX valued around 500 million, and above 10 billion were performed; coupled with comparison between appropriation and actual results, and literature reviews to uncover the complexities, experienced issues that happened in the process. Process and bias analysis were performed to provide solution. Reviews were made on Decision Executive (DE)/Decision Review Board (DRB) effectiveness, market price intelligence, high-grading or project sequencing options, external alignment, optimum time period of investment, biases encountered and how to mitigate them. To mitigate above identified issues, inclusion of mitigation in the FID process, through DE/DRB alignment, project sequencing, market condition scenarios, technology maturity review, debiasing methods, external stakeholder engagement, and optimize time to FID, including transformation and implementation process is presented as part of the study’s conclusion.